2018
DOI: 10.3390/rs10030357
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Rank Defect and Network Effect in Processing the CMONOC Network on Bernese

Abstract: High-precision GPS data processing on Bernese has been employed to routinely resolve daily position solutions of GPS stations in the Crustal Movement Observation Network of China (CMONOC). The rank-deficient problems of the normal equation (NEQ) system and the network effect on the frame alignment of NEQs in the processing of CMONOC data on Bernese still present difficulties. In this study, we diagnose the rank-deficient problems of the original NEQ, review the efficiency of the controlled datum removal (CDR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The velocity field of the GNSS station is obtained by analyzing the coordinate time series of the station. The results showed that the average error in the horizontal velocity field is about 0.2~0.3 mm/yr, and the average error in the vertical velocity field is about 0.5 mm/yr [39,40].…”
Section: Datamentioning
confidence: 99%
“…The velocity field of the GNSS station is obtained by analyzing the coordinate time series of the station. The results showed that the average error in the horizontal velocity field is about 0.2~0.3 mm/yr, and the average error in the vertical velocity field is about 0.5 mm/yr [39,40].…”
Section: Datamentioning
confidence: 99%
“…Firstorder ionospheric delays are eliminated by means of the ionosphere-free linear combination of GPS observations, and higher-order terms are modeled as recommended in Petrie et al (2010). Satellites orbits and the ERPs are introduced from reprocessed (1999-2015) and regular (2015-2019) CODE products, respectively, to assure the consistency of TRF in the daily solution (Wu et al 2018). Meanwhile, they are recommended to be retained fixed in the final least squares estimation of the position parameters, together with phase ambiguities resolved as much as possible and geometrical correlations among GPS stations fully considered (Dach et al 2009).…”
Section: Daily Processingmentioning
confidence: 99%
“…Following the suggestion from Wu et al (2018) on the processing of CMONOC GPS data, we sequentially reprocess all daily NEQs. As an example, we present the eigenvalue properties of two coordinate NEQs on the day of 2014, the original one and the filtered one with frame-origin-related TRF contents fully removed, respectively.…”
Section: Rank Defect Analysis and Trf Strippingmentioning
confidence: 99%
See 2 more Smart Citations